The role and achievements of the International Federation of Air Line Pilots’ Associations (IFALPA) between international governmental and non-governmental aviation organizations - Капустинський, Олексій Андрійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
In the article there has been made an attempt to summarize the assessment of the main role of IFALPA, to distinguish this organisation from other international civil aviation organisations (ICAOs). There also has been covered the organisational structure and specifics of IFALPA, examined its achievements during the entire period of its existence and its significance in the changing world of the civil aviation.